Modeling and Optimization of PET Filament Making Machine Control System Based on Response Surface Methodology - Deni Nur Fauzi; Pradhana Kurniawan; Imam Junaedi; Rendi Pambudi Wicaksono; Nabila Bilqis Mahardi (Jurnal E-Komtek, 2025)
This study aims to model and optimize the control system of a PET filament making machine using Response Surface Methodology (RSM). Two main variables, namely extrusion temperature and winding speed, were analyzed through the Central Composite Design experimental design with the help of Design-Expert 13 software. A quadratic model was developed to predict the filament diameter, and the results of the analysis of variance showed that the model was statistically significant and able to represent the nonlinear relationship between variables. Optimization based on the desirability function produced optimum operating conditions at a medium temperature and winding speed range. Experiments showed that the combination of a temperature of 240–245 °C and a speed of 9–12 rpm produced a consistent filament diameter of 1.7 mm with 70–80% flexibility and a smooth surface.